STRATEGI PENGEMBANGAN USAHA FURNITURE MENGGGUNAKAN PENDEKATAN SWOT - I Ismawati; Abdul Rahim; Alief Hakim Abiansyah (Fakultas Ekonomi dan Manajemen, 2023)
This aims study to the strategy in developing the furniture business at UD. Abbas Jaya, Sumbawa Regency. This research is a field research that uses descriptive research methods. The type of data used is qualitative data in the form of research informants' answers regarding the object of research collected directly from research informants through interviews. The research informants in this study amounted to 10 people consisting of business owners, managers, employees and consumers of UD. Abbas Jaya Furniture, Sumbawa Regency. Data analysis in this study used the SWOT analysis technique to determine the weaknesses and strengths in the internal environment, and threats and opportunities in the external business environment of UD. Abbas Jaya furniture, Sumbawa Regency. The results of the research show that the furniture business of UD. Abbas Jaya, Sumbawa Regency has enormous potential to be developed. Through the SWOT analysis, several alternative strategies were obtained in an effort to develop the furniture business of UD. Abbas Jaya, Sumbawa Regency, namely improving product quality, providing optimal service, increasing promotions by giving discounts, preparing raw material stocks for production to avoid scarcity, and building relationships with raw material suppliers. By implementing these strategies, it is expected to increase consumer satisfaction so that it will create loyalty among consumers. Thus, the company will have immunity from competitors and win the competition.